Behavioural changes in dairy cows with lameness in an automatic milking system - Miguel-Pacheco, G.G.; Kaler, Jasmeet; Remnant, J.G.; Cheyne, Lydia; Abbott, Caroline; French, Andrew P.; Pridmore, Tony P.; Huxley, Jonathan N. (Elsevier, 2013)
There is a tendency worldwide for the automation of farms; this has included the introduction of automatic milking systems (AMS) in the dairy industry. Lameness in dairy cows is highly prevalent and painful. These impacts potentially affect not only animal welfare, but also farm economies. Three independent observational studies were carried out to assess the impact of lameness on the behaviour of zero grazed high yielding Holstein cows managed in an AMS. The aim of the first study was to examine the impact of lameness on rumination time, the second study investigated differences between lame and sound dairy cows in total eating time and the third study assessed the impact of lameness on milking behaviour (frequency and time of visits to the AMS). In the first study data from 150 cows were used to analyse rumination (collected using rumination collars) for the 48hr following locomotion scoring. A multilevel linear regression demonstrated that lameness had a small but significant negative association (coefficient: -7.88 (SE: 3.93)) with rumination. In the second study the behaviour of eleven matched lame and sound pairs of cows at the feed face was analysed for 24 hours after locomotion scoring. Each feeding behaviour variable (total duration time, frequency of feeding bouts and length of bouts) was analysed using individual single level regression models. There was a significant negative association between total feeding time and lameness (coefficient: -73.65 (SE: 25.47)) and the frequency of feeding bouts and lameness (-9.93 (2.49)). Finally, the third observational study used 38 matched pairs of lame and sound cows. Data on the number and timings of visits to the AMS were collected for 24 hours after each locomotion score and analysed using a binomial logistic regression model. There was a significant difference in AMS visits between groups; lame animals visiting the robot less frequently than sound cows (median difference 0.50 milking visits; T = 256.0; N = 25; p = 0.01) and lame cows were 0.33 times less likely to visit the AMS between 24:01 and 06:00. Results from these studies reveal that lameness in an AMS affected feeding behaviour, rumination and AMS visits. All of these impacts are likely to have negative consequences for farm profitability, but also implications for the health and welfare of the animals.